Aspiration of Public-Private Partnership Projects' Risk Management Supported on Probabilistic Linguistic Terms amid Weakened Hedges. (22nd April 2021) - Sun, Yunpeng; Ahmad, Muneeb; Rui, Li; Ahmad, Saleem; Khan, Yousaf Ali
Abstract : The provision of risk involved in a deal for a public-private partnership (PPP) is an essential aspect of triumph that should be based on the best smart party's opinion to organize it. This study anticipated the importance of risk management in PPP projects to adjust the risk management dilemma of the PPP projects' pedestal on the P-LTWHs with a new notion of FMEA. The dynamic linguistic expressions, P-LTWHs, were suggested in the theoretical aspect to articulate decision-makers' assessments, who take the reluctant information with weakened hedges and the likelihood of the linguistic information into account. Besides, the biprojection technique was used to rank risk management problem failure modes in a PPP project. The probabilistic linguistic terms with compromised hedges evaluate the risk management of the novel failure mode and impact analysis (NFMEA) and rank failure modes with the biprojection technique (P-LTWHs). This study also shows that it is possible to spread risks based on fuzzy set theory among public-private parties effectively. Likewise, with the biprojection practice of LTWHs with the VIKOR technique of P-LTWHs, the predicted model is estimated.